Magnetization switching through giant spin–orbit torque in a magnetically doped topological insulator heterostructure - Fan, Yabin; Upadhyaya, Pramey; Kou, Xufeng; Lang, Murong; Takei, So; Wang, Zhenxing; Tang, Jianshi; He, Liang; Chang, Li-Te; Montazeri, Mohammad; Yu, Guoqiang; Jiang, Wanjun; et al. (Nature materials, 2014)
Recent demonstrations of magnetization switching induced by in-plane current in heavy metal/ferromagnetic heterostructures (HMFHs) have drawn great attention to spin torques arising from large spin–orbit coupling (SOC). Given the intrinsic strong SOC, topological insulators (TIs) are expected to be promising candidates for exploring spin–orbit torque (SOT)-related physics. Here we demonstrate experimentally the magnetization switching through giant SOT induced by an in-plane current in a chromium-doped TI bilayer heterostructure. The critical current density required for switching is below 8.9 × 10 4 A cm −2 at 1.9 K. Moreover, the SOT is calibrated by measuring the effective spin–orbit field using second-harmonic methods. The effective field to current ratio and the spin-Hall angle tangent are almost three orders of magnitude larger than those reported for HMFHs. The giant SOT and efficient current-induced magnetization switching exhibited by the bilayer heterostructure may lead to innovative spintronics applications such as ultralow power dissipation memory and logic devices. Heterostructures consisting of ferromagnets and heavy metals have become a focus of interest because their strong spin–orbit coupling allows for efficient current-induced magnetization switching phenomena. Now, a magnetically doped topological insulator bilayer is shown to display a range of appealing characteristics for current-induced magnetization switching, including a significantly enhanced efficiency.